The archaeology of the Ostraca House at Israelite Samaria: epigraphic discoveries in complicated contexts - Tappy, Ron E. (The annual of the American Schools of Oriental Research, 2016)
Introduction and background -- Horizontal axis : the building's original footprint and surrounding area -- Vertical axis : the building's complex depositional history -- Ceramic considerations -- The Samaria ostraca and modern scholarship -- Back to the backstory : the characters and concerns behind the Harvard expedition to Samaria -- Appendix A: Ostraca : provenance data and vessel descriptions -- Appendix B: Ostraca : sequence of discovery -- Appendix C: Non-epigraphic pottery with provenance data matching those of the ostraca -- Appendix D: D.G. Lyon's report to the president of Harvard University for the academic year 1898-1899, showing the financial generosity of Jakob Heinrich Schiff -- Appendix E: Reisner's field drawings of selected ostraca